2016
DOI: 10.1111/aos.13239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of allergy and atopy on new onset of uveitis

Abstract: Our results argue against a substantial influence of allergies and atopy on the onset of uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A recent analysis (2012-2014) did not demonstrate a statistically significant correlation between the impact of atopy and the onset of uveitis (p = 0.494) [58].…”
Section: Uveitismentioning
confidence: 87%
“…A recent analysis (2012-2014) did not demonstrate a statistically significant correlation between the impact of atopy and the onset of uveitis (p = 0.494) [58].…”
Section: Uveitismentioning
confidence: 87%
“…Among these, evidence suggests that cataract surgery is causally involved in RRD occurrence in children; in recent study, a 5.5% risk for RRD is estimated within first 10 years after cataract surgery in childhood [ 12 , 36 ]. It is also known that cataract is one of the various complications of uveitis [ 37 , 38 ]. In addition, CTD is frequently accompanied by uveitis, and cataract may be caused by steroids, which are mainly used for the treatment of CTD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uveitis was not detected in any of our patients either. Likewise, an article about the impact of allergy and atopy on new onset of uveitis in Germany demonstrated that there is no significant correlation between atopy and new onset of uveitis [26] . Atopy seems to be an important factor in the occurrence of keratoconus [27] .…”
Section: Discussionmentioning
confidence: 99%